2011
DOI: 10.1093/humrep/der156
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptives and endometriosis: the past use of oral contraceptives for treating severe primary dysmenorrhea is associated with endometriosis, especially deep infiltrating endometriosis

Abstract: Our data indicate that a history of OC use for severe primary dysmenorrhea is associated with surgical diagnosis of endometriosis, especially DIE, later in life. However, this does not necessarily mean that use of OC increases the risk of developing endometriosis. Past use of OC for primary dysmenorrhea may serve as a marker for women with endometriosis and DIE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(103 citation statements)
references
References 43 publications
3
91
1
8
Order By: Relevance
“…For this purpose, we confronted various characteristics of OC use and the surgical diagnosis of endometriosis, histologically graded as superficial, ovarian endometrioma, or DIE. 21 In 410 patients with histologically proven endometriosis, we confirmed the association between past OC users and endometriosis (OR: 2.79, 95% CI: 1.74, 5.12; P 5 .002). This association was observed for all rAFS * classifications.…”
Section: Oral Contraceptives Prescribed For Adolescent Dysmenorrheasupporting
confidence: 66%
“…For this purpose, we confronted various characteristics of OC use and the surgical diagnosis of endometriosis, histologically graded as superficial, ovarian endometrioma, or DIE. 21 In 410 patients with histologically proven endometriosis, we confirmed the association between past OC users and endometriosis (OR: 2.79, 95% CI: 1.74, 5.12; P 5 .002). This association was observed for all rAFS * classifications.…”
Section: Oral Contraceptives Prescribed For Adolescent Dysmenorrheasupporting
confidence: 66%
“…44 Other studies were small including a total of 512-976 women with 168-410 endometriosis cases. 10,12 This study also has limitations, which should be considered. It is a cross-sectional study where information was collected at one time point with no follow-up, which probably affected the prevalence of endometriosis.…”
Section: Strength and Weaknessesmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] A link between use of oral contraceptives (OCs) and endometriosis is still uncertain. Researchers have observed an increased risk, 12 a protective effect, 13 and even no association 14 between OC and endometriosis. It has been suggested that up to 50% of infertile women have endometriosis; however, a causal link has not yet been demonstrated.…”
mentioning
confidence: 99%
“…The best way of diagnosis is laparoscopy or laparotomy, along a histological confirmation of macrophages with hemosiderin, endometrial epithelium and endometrial glands or stroma. Malignant transformation has been observed in 0, 6 presented ovaric endometriosis. GnRH analogues are broadly used as medical treatment, while danazol is less used because of its androgenic effects.…”
Section: Endometriosis In the Inguinal Channel: A Casementioning
confidence: 99%
“…Chapron et al, realizó un estudio transversal de 566 pacientes con diagnóstico quirúrgico de endometriosis ovárica, peritoneal e infiltrante profunda; para evaluar si estaba asociado a anticonceptivos orales. Concluyeron que las pacientes que usaban anticonceptivos orales por dismenorrea asociaban principalmente endometriosis profunda infiltrativa, cabe destacar que aclaran que no significa que los anticonceptivos orales aumenten el riesgo d endometriosis [6]. Por otro lado, el uso cíclico de anticonceptivos orales monofásicos puede ayudar en el manejo de la endometriosis.…”
Section: Definición Y Epidemiologíaunclassified